Geographies of sexual commerce and the production of prostitutional space: Victoria, British Columbia, 1860–1914 - Dunae, Patrick (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2008)
AbstractThe essay considers the geography and economic significance of the sex trade in Victoria, British Columbia, a city that has historically associated itself with notions of gentility and images of English country gardens. The essay problematizes that image. Influenced by the spatial turn in the Humanities and informed by Henri Lefebvre’s ideas on the production of space, the production of prostitutional space is the focus of this piece. The essay discusses how and why space was demarked by local authorities for what Foucault called “illegitimate sexualities.” It delineates geographies of sexual commerce in Victoria and invites questions about sexuality in other Canadian and American cities, as well as other British colonial cities. This piece is a tentative step towards mapping moral geographies in nineteenth century cities and placing them within a broader temporal, societal, spatial, and theoretical framework.